Narrativas de sofrimento e trabalho profissional do Serviço Social da Previdência Social em tempos de indústria 4.0* - Souza, Edvânia Ângela De [UNESP]; Anunciação, Luís (Cortez Editora Ltda, 2020)
The current economic, social, and political changes have impacts on the work environment and the psychosocial conditions of the workers. In this study, we discuss the professional work of Social Workers (SW) working in working in the Brazilian social security system, using a mixed-methods approach including the results obtained through standardized scales, focus groups, and interviews conducted between 2014 and 2019. Despite the results obtained by psychometric systems suggest a non-negative outcome, the other methods could reveal that work generates a kind of silent, invisibility and is marked by distress and/or suffer.

Atuais mudanças econômicas, sociais e políticas geram impactos nos ambientes e nas condições psicossociais de trabalho. Neste texto, discute-se o trabalho de Assistentes Sociais (AS) atuantes na Previdência Social (PS), a partir da combinação de resultados obtidos por meio de projeto de pesquisa em andamento, cuja metodologia faz uso de escalas padronizadas, grupos focais e entrevistas realizadas entre 2014 e 2019. Apesar de não haver resultados negativos obtidos pelos instrumentos padronizados, as outras técnicas puderam revelar que o trabalho gera um tipo de sofrimento mudo, invisível e marcado pela angústia e frustração.
Narratives of Suffering and Professional Work of Social Workers in Social Security in the Industrial times 4.0
Keywords: Industry 4.0 or 4th Industrial Revolution (4th RI); Social Security; Social Work; Work distress; Indústria 4.0 ou 4ª Revolução Industrial (4ª RI); Seguridade Social; Serviço Social; Sofrimento no trabalho